2010
DOI: 10.1021/ja100780p
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stalling after Mismatches on the Error Catastrophe in Nonenzymatic Nucleic Acid Replication

Abstract: The frequency of errors during genome replication limits the amount of functionally important information that can be passed on from generation to generation. During the origin of life, mutation rates are thought to have been quite high, raising a classic chicken-and-egg paradox: could nonenzymatic replication propagate sequences accurately enough to allow for the emergence of heritable function? Here we show that the theoretical limit on genomic information content may increase substantially as a consequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
143
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(160 citation statements)
references
References 32 publications
(48 reference statements)
11
143
0
Order By: Relevance
“…It turns out that common structures are not only easier to find, but also withstand higher mutation rates and are therefore more evolvable. Although our simulations were not aimed to explain any specific scenario, the molecule length used here (n = 35) leads to critical error rates which are compatible with a recent experimental study for nonenzymatic nucleic acid replication (Rajamani et al, 2010).…”
Section: Summary and Discussionsupporting
confidence: 79%
“…It turns out that common structures are not only easier to find, but also withstand higher mutation rates and are therefore more evolvable. Although our simulations were not aimed to explain any specific scenario, the molecule length used here (n = 35) leads to critical error rates which are compatible with a recent experimental study for nonenzymatic nucleic acid replication (Rajamani et al, 2010).…”
Section: Summary and Discussionsupporting
confidence: 79%
“…Primer-extension following a mismatch can be much slower than following a Watson-Crick base-pair. Such post-mismatch stalling was originally noticed in enzymatic reactions [31,32] but is also significant in a non-enzymatic DNA template-copying model system [33]. The beneficial effect of post-mismatch stalling on fidelity is a consequence of the fact that those templates that are completed first tend to be the most accurately copied.…”
Section: Fidelity Of Template Copying Chemistrymentioning
confidence: 88%
“…3'-amino-2', 3'-dideoxynucleotides have been used as model systems by the groups of Orgel [18], Richert [25] and Szostak [26]. After analyzing Orgel's work, we concluded that nontemplated cyclization of the single strands can be reduced if the rate of ligation to elongate the double strands is enhanced.…”
Section: Design Of the Model Systemmentioning
confidence: 99%